A study on behavioural effects of laboratory rats (albino wistar) after the sub-chronic noise stress - J. A. P., Bodhika; J. R. I. A., Jayakody (International Journal of Research in Medical Sciences, 2018)
Background: Humans and animals can hear a wide range of sound frequencies. If the sense of hearing is impaired, both man and animal cannot fare well in their respective environments. Present study is aimed to investigate the behavioral effects following the sub-chronic noise stress of a rat species, Albino Wistar. Methods: The sound source consists of a set of speakers, GWINSTEK AFG-2000 series function generator and an amplifier. Sound levels and frequencies were monitored by B and K type 2250 sound level meter. Six adult Albino Wistars were exposed to sound frequencies of 1-20 kHz, at intervals of 1 kHz at LAeq of 70-80 dB for 5minute periods and their behavior was recorded. In the second test four adult rats were randomly divided into control and test groups. The test animals were exposed to noise of 7, 8, 9 and 10 kHz for 4hrs daily while keeping the control group in same room for same period of time without exposing to the sound. Locomotive activity, increase of defection and decrease of social activities, of rats was assessed by open field test (OFT). Anxiety and depressive behavior were monitored by elevated plus maze test (EPM) and tail suspension test (TST). Results: A different behavior in rats was observed in frequency range of 7-10 kHz. At the beginning of exposure, all rats were huddled in a group and then some were frozen into motionless stance. A less time spent and less number of entries in open arm was noticed in test sample compared to the controls in the EPM test. A tendency to move to open field compared to controls was identified in OFT. The TST revealed that a significant increase in immobility time, which indicates a depression like behavior of noise stressed rats compared to controls. Conclusions: According to the study the most effective noise frequency range for rats is 7-10 kHzl.